Efeito agudo do aquecimento realizado através de exercícios dinâmicos e jogo de futebol em campo reduzido sobre a agilidade em crianças - Coledam, Diogo Henrique Constantino; Santos, Júlio Wilson dos [UNESP] (Universidade Estadual de Maringa, 2011)
The aim of this study was to evaluate the effect of warm up performed by dynamic exercises (DYN) and small sided soccer game (SOC) on agility with ball (AB) and agility without ball (AG). Eighteen children of both genders (n=18) performed the AB and AG tests after three conditions: without warm-up (WWU), DYN and SOC. The effects of DYN and SOC warm-ups on AG test was higher than WWU (p<0,05) and it was similar among them (WWU=12,2 ± 1,0, DYN= 11,3 ± 0,7, SOC=11,4 ± 0,6 s), as well as on AB test (WWU=15,0 ± 2,1, DYN= 14,4 ± 2,1, SOC=14,0 ± 1,6 s). Results in both tests were similar by gender, except in AB test performed with DYN warm-up, in girls. SOC is an effective warm-up protocol for agility tests with or without ball and can be used before agility motor tasks in children.
Acute effects of warm-up performed by dynamic exercises and small sided soccer game on agility in children
Keywords: Child; Soccer; Sport